2008
DOI: 10.1016/j.pupt.2007.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Fluticasone, but not salmeterol, reduces cigarette smoke-induced production of interleukin-8 in human airway smooth muscle

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting galley proof before it is published in its final citable form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…In this context patients with COPD who smoke or who have stopped smoking are known to experience continuing oxidative stress 37 that might be associated with relative steroid resistance. 38,39 We showed that GSH significantly inhibited CSE-mediated IKKa and IKKb activity and that FP moderately but significantly improved its downregulatory effects on IKKa activity in the presence of GSH. These results suggest that the reduced ability of FP to inhibit IKKa and IKKb is sustained by unresolved oxidative stress and might in part explain the poor or absent response to glucocorticosteroids that characterizes COPD.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In this context patients with COPD who smoke or who have stopped smoking are known to experience continuing oxidative stress 37 that might be associated with relative steroid resistance. 38,39 We showed that GSH significantly inhibited CSE-mediated IKKa and IKKb activity and that FP moderately but significantly improved its downregulatory effects on IKKa activity in the presence of GSH. These results suggest that the reduced ability of FP to inhibit IKKa and IKKb is sustained by unresolved oxidative stress and might in part explain the poor or absent response to glucocorticosteroids that characterizes COPD.…”
Section: Discussionmentioning
confidence: 89%
“…These results suggest that the reduced ability of FP to inhibit IKKa and IKKb is sustained by unresolved oxidative stress and might in part explain the poor or absent response to glucocorticosteroids that characterizes COPD. 39 In addition, the finding that the presence of GSH potentiates the effects of FP on IKKa and IKKb activity, generating a similar modulation of both kinases by glucocorticosteroids, suggests that targeting cigarette smokeinduced oxidative stress might have beneficial outcomes in the treatment of COPD. 40 IL-8 synthesis is highly NF-kB dependent, and this process requires both IKKa and IKKb activity.…”
Section: Discussionmentioning
confidence: 99%
“…CS has been shown to induce IL-8 release from ASM cells (10,30,31). This may involve oxidative stress, as the CSinduced IL-8 release was inhibited by glutathione pretreatment and associated with increased expression of heme oxygenase-1 (30).…”
Section: Discussionmentioning
confidence: 99%
“…risk factor of COPD, has been shown to induce the release of interleukin-8 (IL-8) from ASM cells, which positions these cells to contribute to increased neutrophil influx to the airways (10,30,31). The proportion of airways containing neutrophils, as well as other inflammatory cells, has been found to correlate with COPD severity (15).…”
mentioning
confidence: 99%
“…Also, in vitro studies have shown that airway smooth muscle cells produce IL-8 in response to many inflammatory mediators implicated in COPD, including TNF-a [42], IL-17 [43] and neutrophil products, such as LL-37 [44], bacteria [45] and cigarette smoke [18]. Combining cigarette smoke with TNF-a results in a synergistic increase in IL-8 release [46]. Our data also show that muscarinic receptor agonists can act in concert with cigarette smoke to induce the production of IL-8 by airway smooth muscle cells, suggesting that these cells, in addition to epithelial cells and inflammatory cells, could play an important role in the inflammatory process involved in neutrophil recruitment and exacerbations of COPD.…”
Section: Discussionmentioning
confidence: 99%